Differences in the Effect of Sacroiliac Joint Mobilization and Joint Stretches on Lumbar Range of Motion in Sacroiliac Joint Dysfunction–Related Low Back Pain - Nugraha, Rahmat; Hasbiah; Wahyudi, Indah Try; Sudaryanto; Erawan, Tiar; Tang, Aco (Physiotherapy, Exercise, and Rehabilitation Sciences Journal, 2026)
Aims: This study aimed to determine the difference in the effects of Sacroiliac Joint Mobilization and Sacroiliac Joint Stretches on improving lumbar ROM in low back pain caused by sacroiliac joint dysfunction. This quasi-experimental research used a randomized pre-test-post-test two-group design. Methods: The study involved 20 participants, randomly allocated into two groups: 10 participants in Group 1 receiving Sacroiliac Joint Mobilization and 10 participants in Group 2 receiving Sacroiliac Joint Stretches. Data were collected by measuring lumbar ROM during flexion and extension in both the pre-test and post-test phases. Results: Paired sample t-test analysis showed significant improvements in ROM for both groups with p = 0.000. Furthermore, the independent sample t-test revealed a significant difference between the two groups, with p = 0.034 for flexion (mean difference: 15.2 in Group 2 > 9.6 in Group 1) and p = 0.001 for extension (mean difference: 14.7 in Group 2 > 10.2 in Group 1). Conclusion: These findings indicate that Sacroiliac Joint Stretches provide a greater improvement in both lumbar flexion and extension ROM compared to Sacroiliac Joint Mobilization in patients with low back pain caused by sacroiliac joint dysfunction.